Empowering Excellence: The Impact of Corporate Governance and Employee Competence on Performance - Putri, Eva Kumala Sapna; Achmad, Nur (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2024)
This study investigates the impact of employee competence and good corporate governance (GCG) on employee performance, with job satisfaction as a mediating variable, focusing on Bank BJB Bandung. Its uniqueness lies in its specific emphasis on the banking sector, particularly regional banks in Indonesia, which are underexplored in prior research. While many studies examine the general relationship between corporate governance, competence, and performance, this research integrates job satisfaction as a mediator in this unique context. The study employs a quantitative approach, with a population consisting of Bank BJB Bandung employees. Using purposive sampling, 80 respondents were selected, and data were collected through questionnaires designed on a Likert scale. The analysis utilizes PLS-SEM with SMARTPLS 3.2 software, offering a robust framework for testing mediating effects. PLS-SEM comprises two components: The Inner model, which examines relationships between latent variables, and the Outer model, which assesses validity and reliability. The findings reveal that job satisfaction mediates the relationship between employee competence and GCG on employee performance. This study contributes theoretically by emphasizing mediation within the context of regional banking and offers methodological innovation through the application of PLS-SEM for analyzing mediating variables.